UNDERSTANDING PHYTOTHERAPY OF ALZHEIMER’S DISEASE: LAST DECADE AND COMING FUTURE: Life Sciences-Neuroscience - CHAKRABARTY, MRINMOY; THAWANI, VIJAY (International Journal of Life Science and Pharma Research, 2011)
Years of research have not been able to tame the relentless progression of Alzheimer’s disease (AD). With some of the most promising forerunner therapeutic molecules failing in late phase clinical trials recently and the existing modern therapies yielding only modest, short term benefits at the cost of different side effects, the focus has more strongly shifted on the plant derived molecules which have been claimed to exert significant anti dementic effects over the ages and as a matter of fact have come up with impressive findings in rigorously conducted experimental laboratory studies and randomised clinical trials. The review summarizes the core salient findings in this domain in the past ten years.